A Study Of Sustainable Marketing After Pandemic Era In Indonesia - Puspitaloka Mahadewi, Erlina; Asih, Daru; Permana, Dudi; Jumarno, Jumarno (Publisher Cv. Inara, 2024)
The present study reports the first comprehensive study about rebuilt the business resilience is very important to achieve the rise healthcare industry especially hospital, because of their important role in the national economy. Most business organizations in Indonesia have experienced disruption caused by the covid-19 pandemic, not a few have ended up bankrupt and unable to survive. This research aims to formulate a framework for hospital marketing and business revival during and after a crisis like covid-19. The aim of this research is to analyze the influence of perceived benefits and culture in affecting clean and healthy living behaviors (PHBS) for patients, with the mediation of religiosity. This study is classified as quantitative research aimed at testing hypotheses statistically. The research subjects are drawn from 150 patients in a shariah hospital using survey research, resulting in the in-patient informant from two group of moslem hospitas group with the questionare. The research findings indicate that perceived benefits and culture, have significant impact on religiosity and PHBS. Religiosity plays a mediating role connecting perceived benefits and culture to PHBS in the shariah hospital. It is hoped in the future that hospital can restore their business conditions and be able to revive after the pandemic with the sustainable marketing.